Gender Transformative Methodologies CoP. Intersectionality: A study on gender equality and social inclusion as part of the Climate Adaptive, Inclusive, Nature-based Aquaculture (CAINA) project in Malaysia - Rajaratnam, Surendran; Yap, Tina; Bailey, Arwen (2024)
Insights into integrating the principles of gender equality and intersectionality throughout the research process in a research project on Nature-based Solutions (NbS) in aquaculture. Traditional aquaculture research often overlooks the diverse experiences of those involved. By incorporating gender and social inclusion, they aim to identify all stakeholders (i.e. women, men, youth, indigenous communities and marginalized groups) that play a role in NbS aquaculture. They use a gender equality and social inclusion lens to ensure a comprehensive stakeholder analysis. In addition, they identify the different needs and challenges of different stakeholders in NbS aquaculture.